The description of wrist and shoulder motion of different waterpolo shots using a simple light-trace technique - Clarys, J. P.; Lewillie, L. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
It was the purpose of this study to describe the movement of shoulder and wrist in 5 different waterpolo shots by means of a light trace transfer. As secondary purpose, this technique can be used in combinaison with film in order to compare shoulder and wrist movements in waterpolo more precise.